KONSTRUKSI KEBIJAKAN ANGGARAN: AKSENTUASI DRAMA POLITIK DAN KEKUASAAN (STUDI KASUS KABUPATEN JEMBRANA BALI) - Syarifuddin Syarifuddin (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2011)
The aims of this study, is to analyse how the political interaction, power and politics occurred in budget policy construction. Specifically, the study aims at answering who become the actor behind budget policy, how they think, how they interact to dramatize the policy construct. Method of study employs extended dramaturgy reflecting the development of dramaturgy method proposed by Erving Goffman. This method assumes that during interaction, people not only realize others, but also recognize themselves. Therefore, people not only interact with others, but they interact with themselves symbolically. This interaction is observed in Jembrana local government and society as a unit of analysis.The results of this study are: (1) the accounting man uses politic and power to identify social problem as the base to determine budget policy, (2) In analyzing the identification of education problem as social problem, power must be demanded to reveal the fact because the problem cannot speak about itself, (3) the problem identified should be adjusted to the issue beyond the individual local environment and individual life coverage, and (4) the most prominent text with budget policy “constructive” view at Jembrana municipality corresponds with view on “justice” and “truth” along with “ngaya” symbolizing of “the freedom”. Ngaya pertains to an “altruistic” politic, meaning to serve the community and the government, to get better post-reincarnation life.